PERBANDINGAN JENIS PEWARNA ALAMI UNTUK PEWARNAAN PREPARAT BATANG BAYAM (Amaranthus spinosus L.) DALAM PRAKTIKUM JARINGAN TUMBUHAN - Nakti Kholifah; Suharno Zen; Hening Widowati (EDUBIOLOCK, 2024)
The aim of this study were 1) to determine the strength of the absorption of various types of natural dyes of dragon fruit, beet fruit, blueberry fruit on spinach stem preparations (Amaranthus spinosus, L.), 2) to determine the results of the absorption of the best types of natural dyes on spinach stem preparations (Amaranthus spinosus, L.), 3) to make the results of research on the absorption of natural dye types as practicum preparations in plant tissues This type of research is qualitative descriptive experimental research. This study used 3 treatments 3 times repetition using dragon fruit dyes, beet fruit and blueberry fruit and 1 positive control using synthetic dyes in the form of safranin. Data analysis in this study is presented in the form of non-statistical qualitative descriptive analysis. Based on the results of the study, the strength of the absorption of dye types has different absorption strengths seen from the results of RGB (Red, Green, Blue) values, luminance values, ratio values and overall RGB (Red, Green, Blue) values from each treatment. The best type of dye absorption starts from dragon fruit, blueberry fruit, beet fruit, and 1 positive control safranin dye. The results of the study were declared "feasible" to be used as a coloring preparation for plant tissue practicum.